2005
DOI: 10.1016/j.ajem.2004.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of acute renal failure and need for hemodialysis among ED patients with rhabdomyolysis

Abstract: Acute renal failure and need for HD are common complications of rhabdomyolysis. Except for initial serum Cr and blood urea nitrogen, clinical and laboratory factors were not reliable predictors for the development of ARF or need for HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 36 publications
7
58
1
2
Order By: Relevance
“…Fernandez et al [13] found that the only variable that was predictive of both ARF and need for hemodialysis in separate multivariate regression models was initial serum creatinine. No patient developed ARF with initial creatinine less than 1.7 mg/dL [13]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernandez et al [13] found that the only variable that was predictive of both ARF and need for hemodialysis in separate multivariate regression models was initial serum creatinine. No patient developed ARF with initial creatinine less than 1.7 mg/dL [13]).…”
Section: Discussionmentioning
confidence: 99%
“…No patient developed ARF with initial creatinine less than 1.7 mg/dL [13]). On the other hand, the present study showed that only 9 of the 15 (60%) patients who developed ARF had significantly raised initial creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies lack the patient-level data needed to adequately adjust for comorbid illness, and utilize limited registry data to categorize AKI (15). Small sample sizes of studies with patientlevel data have had limited ability to detect novel mediators of mortality or the provision of dialysis after the occurrence of AKI (16,17). Finally, few studies have accurately established the date of the onset of AKI.…”
Section: Introductionmentioning
confidence: 99%
“…AKI is a serious and often life-threatening complication of rhabdomyolysis and requires immediate diagnosis and emergency treatment (9,33,34). AKI is believed to be due to decreased extracellular volume, which results in renal vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Medical Science and Discovery, 2016; 3(1): [28][29][30][31][32][33][34] rhabdomyolysis-induced AKI is higher in patients with CK levels at admission more than 5000 IU/L (16).…”
mentioning
confidence: 99%